PENGARUH LATIHAN POSITIVE HOPS TERHADAPWAKTU REAKSI PADA PERMAINAN BOLA VOLI PUTRA TIM MTSN ANDALAN PEKANBARU - Putri Wulandari Wulandari; Ramadi '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, This research want to know is there any effect of Positive Hops  exercise toward reaction time of MTSN Andalan Pekanbaru man vollyball club, soget develop ability reaction time  when defence, is receive the ball from opponent and getting win. This research was experimental research. The population in this research was the man athletes of vollyballMTSN Andalan Pekanbaru, while the sample was all of the manathletes MTSN Andalan Pekanbaru, the total of 12. Sampling technique used in this research was Total Sampling. According to Arikunto (2006: 134), if the population are less of 100